Influence of Operating Parameters and System Design on Efficiency of Biomass and Biogas Based SOFC Systems. (30th May 2017) - Herrmann, Stephan; Hauck, Maximilian; Geis, Michael; Fendt, Sebastian; Gaderer, Matthias; Spliethoff, Hartmut
Abstract : The presented work investigates utilization of biogas and syngas from biomass gasification in different system designs. This is done using a thermodynamic SOFC model built in Aspen Plus. With the model, the influence of different fuel pre-treatment and pre-reforming options are compared at a fixed stack size. Furthermore the effect of anode off-gas recirculation, as well as the choice of fuel utilization are studied. Results show, that depending on the fuel, system design and parameters the electrical efficiency of the fuel cell alone can vary between 35 and 71%. System AC net efficiencies reach from 30 to 64%. Finally a new system configuration is investigated, which is based on recovery of H2 from the anode exhaust using a water gas shift membrane. For this new configuration an efficiency of 73% is calculated.